Qualidade fisiológica de sementes de cevada influenciadas pela época de colheita - Silva, Airam Fernandes da (2007)
The purpose of this work was to verify the physiologic quality of seeds of two barley cultivars, in different harvesting times. The experiment was installed in a field of barley production for brewing industry, in Piratini, RS during 2006 growing season. The analyzed seeds were cultivar MN858 and SCARLETT, harvesting starts when panicles were with a moisture around 30% (physiologic maturation) and subsequent harvesting in regular intervals of ten days. To determine the physiologic quality of the seeds the following variables were accomplished: germination; first counting of germinated seeds; tetrazolium; accelerated aging; weight of one thousand seeds; hectoliter weight; lenght of the aerial and root systems; dry and fresh matter of root and aerial systems; and electrical conductivity. The experimental design used was an entirely randomized with four replications and the means were compared by Duncan multiple ranger test (5% of significance). It was concluded that barley cultivars studied, have dormancy just after harvested; with harvesting time delay, cultivar MN858 increases, intensely, dormancy, while, in cultivar SCARLETT, dormancy tends to decrease; seeds of cultivar MN858 presents better physiologic quality when harvested with a moisture of 22,8%, while in cultivar SCARLETT, with a moisture of 18,7%; seeds of both cultivars submitted to heat and water stress has their physiological quality reduced and there was a reduction in the specific gravity of seeds with harvesting time delay.